Chemovirotherapy of Pancreatic Adenocarcinoma by Combining Oncolytic Vaccinia Virus GLV-1h68 with nab-Paclitaxel Plus Gemcitabine - Binz, Eike (Mol Ther Oncolytics, 2017)
Oncolytic viruses have proven their therapeutic potential against a variety of different tumor entities both in vitro and in vivo. Their ability to selectively infect and lyse tumor cells, while sparing healthy tissues, makes them favorable agents for tumor-specific treatment approaches. Particularly, the addition of virotherapeutics to already established chemotherapy protocols (so-called chemovirotherapy) is of major interest. Here we investigated the in vitro cytotoxic effect of the oncolytic vaccinia virus GLV-1h68 combined with dual chemotherapy with nab-paclitaxel plus gemcitabine in four human pancreatic adenocarcinoma cell lines (AsPc-1, BxPc-3, MIA-PaCa-2, and Panc-1). This chemovirotherapeutic protocol resulted in enhanced tumor cell killing in two tumor cell lines compared to the respective monotherapies. We were thereby able to show that the combination of oncolytic vaccinia virus GLV-1h68 with nab-paclitaxel and gemcitabine has great potential in the chemovirotherapeutic treatment of advanced pancreatic adenocarcinoma. However, the key to a successful combinatorial chemovirotherapeutic treatment seems to be a profound viral replication, as tumor cell lines that were non-responsive to the combination therapy exhibited a reduced viral replication in the presence of the chemotherapeutics. This finding is of special significance when aiming to achieve a virus-mediated induction of a profound and long-lasting antitumor immunity.